HAK ANAK DALAM PERSPEKTIF AL-QUR’AN - Ida Novita; Pathur Rahman (Qolamuna : Jurnal Studi Islam, 2023)
The purpose of this study is to provide an explanation for: What significance does the Qur'an place on the rights of children? The analytical and descriptive approach of the maudhu'i method is utilized in this study. The findings of the study demonstrate: The Qur'an gives special attention to children. It can be seen from the many verses that talk about children with various terms such as al-walad, ibn, bint, dzurriyyah, shabi, thifl, al-ghulam. In the Qur'an there are 4 typologies of children who are seen as 1) Jewelry, 2) Cooling, 3) Slander/Trial, 4) Enemy to their parents. Therefore, in order for children to truly be a source of happiness, parents should exercise the rights of their children as follows: First, the right to life. Second, the right to clarity. Third, the right to obtain breast milk and bread. Fourth, the right of protection from hellfire. Fifth, the right to fair treatment. Sixth, the right to education. Keywords : Rights, Children, Qur’an